Efektivitas Media Sosial sebagai Sarana Promosi Layanan Investasi di PT Victory International Futures - Fitri Nur Wulansari; M. Isa Anshori (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the effectiveness of social media as a means of promoting investment services at PT Victory International Futures, a futures brokerage company operating in Indonesia. In the digital era marked by the development of information and communication technology, social media has become a strategic marketing tool to increase visibility, attract investor interest, and build relationships with customers. This study uses a literature study approach to review various literature related to digital marketing strategies, the role of social media in promotion, and the dynamics of the futures brokerage industry. This study found that social media, such as Instagram, Facebook, and LinkedIn, have a significant role in increasing brand awareness, expanding market reach, and influencing investment decisions. However, its effectiveness depends on relevant content strategies, consistent interactions, and a deep understanding of target audience behavior. This study also identifies challenges such as intense competition in the digital space and the need to comply with financial marketing regulations. The conclusion of this study confirms that targeted and measurable use of social media can improve a company's image and the effectiveness of investment service promotion, with recommendations to optimize digital content and analytics strategies.